Association between postictal EEG suppression, postictal autonomic dysfunction, and sudden unexpected death in epilepsy: Evidence from intracranial EEG. (February 2023) - Esmaeili, Behnaz; Weisholtz, Daniel; Tobochnik, Steven; Dworetzky, Barbara; Friedman, Daniel; Kaffashi, Farhad; Cash, Sydney; Cha, Brannon; Laze, Juliana; Reich, Dustine; Farooque, Pue; Gholipour, Taha; et al.
Highlights: Intracranial EEG may demonstrate regional postictal EEG suppression (PES) despite simultaneous scalp EEG showing either generalized PES or no PES. The extent of intracranial PES is associated with severity of postictal autonomic dysfunction as measured by heart rate variability. PES duration and extent are similar in non-fatal seizures between patients with and without sudden unexpected death in epilepsy (SUDEP). Abstract: Objective: The association between postictal electroencephalogram (EEG) suppression (PES), autonomic dysfunction, and Sudden Unexpected Death in Epilepsy (SUDEP) remains poorly understood. We compared PES on simultaneous intracranial and scalp-EEG and evaluated the association of PES with postictal heart rate variability (HRV) and SUDEP outcome. Methods: Convulsive seizures were analyzed in patients with drug-resistant epilepsy at 5 centers. Intracranial PES was quantified using the Hilbert transform. HRV was quantified using root mean square of successive differences of interbeat intervals, low-frequency to high-frequency power ratio, and RR-intervals. Results: There were 64 seizures from 63 patients without SUDEP and 11 seizures from 6 SUDEP patients. PES occurred in 99% and 87% of seizures on intracranial-EEG and scalp-EEG, respectively. Mean PES duration in intracranial and scalp-EEG was similar. Intracranial PES was regional (<90% of channels) in 46% of seizures; scalp PES was generalized in all seizures. Generalized PES showed greater decrease in postictal parasympathetic activity than regional PES. PES duration and extent were similar between patients with and without SUDEP. Conclusions: Regional intracranial PES can be present despite scalp-EEG demonstrating generalized or no PES. Postictal autonomic dysfunction correlates with the extent of PES. Significance: Intracranial-EEG demonstrates changes in autonomic regulatory networks not seen on scalp-EEG.